Reconstructing and translating regional cultural ideo-symbols through comparative glocalism: the case of Jiangsu - Meng Xiangchun; Ji Zhinan (Language and Semiotic Studies)
The translation and international communication of regional and national cultural ideo-symbols promote the reception and visibility of cultural identity in a globalized context and contribute to global cultural diversity and intercivilizational appreciation. Jiangsu Province exemplifies China’s broader efforts to construct or reconstruct its cultural identity for this purpose. From its huge wealth of cultural symbols, we propose six most representative interconnected yet autonomous established or reconstructed ideo-symbols, including the traditional Chinese character “蘇,” symbolizing a land of fish, rice, and botanic exuberance; “water paradise,” evoking a water-nurtured land of material affluence and civilizational excellence; “water-rhymed Jiangsu,” highlighting the presence of water in Jiangsu’s classical writings and collective consciousness; “Jiangnan,” often as a poeticized and romanticized space of half-earthly and half-Utopian nature; “harmonious and inclusive Jiangsu,” conveying the triad harmony of humanity, nature, and culture; and “elegant-living Jiangsu,” capturing the ritualistic transformation of everyday life into aesthetic experience and artistic existence. Comparative glocalism, both as a way of thinking and as a practice in translation, offers an effective strategy for introducing these ideo-symbols to international audiences. Through comparative glocalism, these symbols can be translated into globally relevant yet locally grounded entities within accessible discourse, retaining their significance while advancing cross-cultural and intercivilizational dialogue. To this end, we further propose a series of initiatives and practices, including employing digital storytelling and semiotic narratives, enhancing cross-disciplinary, multichannel collaborations, launching cultural exchange programs, optimizing multimodal platforms, engaging with Internet content influencers, developing specialized databases and websites, organizing cultural symbol design competitions, etc. This study offers an integrated, newly constructed newly constructed ideo-symbolic system and communication strategy for the international communication of Jiangsu’s cultural symbols. It may inform and inspire other local or national cultures’ global outreach.